PROSES PENYUSUNAN LAPORAN BENDAHARA DAN LAPORAN KEUANGAN MELALUI APLIKASI SPRINT DAN E-REKON PADA KPPN MEULABOH - Sinta Delviani; Rusdi (Bajang Institute, 2021)
This study aims to describe how the process of preparing the Treasurer's Accountability Report (LPJ) on the SPRINT application and the preparation of Financial Statements on the E-rekon LK application. This research method uses qualitative research methods. Where qualitative research is descriptive research and tends to use inductive analysis and approaches (Rahmat, 2019). With data collection techniques, namely from primary data and secondary data, where primary data was obtained from interviews that were asked directly to the Verification and Accounting Section employees at KPPN Meulaboh and secondary data was obtained from the Ministry of Finance and DJPB websites online. This research was conducted at KPPN Meulaboh Jl.sisingamangaraja, West Aceh Regency. And also this research was carried out from March 2021 to August 2021. However, the problem that sometimes arises is the delay in submitting the LPJ Treasurer and Financial Report to KPPN Meulaboh so that the preparation of LK related to BUN (State Treasurer) is late. The results of the use of these two applications can make the satker or KPPN easy and fast in preparing the LPJ Treasurer and Financial Statements.